A β2-Integrin/MRTF-A/SRF Pathway Regulates Dendritic Cell Gene Expression, Adhesion, and Traction Force Generation - Guenther, Carla; Faisal, Imrul; Uotila, Liisa M.; Asens, Marc Llort; Harjunpää, Heidi; Savinko, Terhi; Öhman, Tiina; Yao, Sean; Moser, Markus; Morris, Stephan W.; Tojkander, Sari; Fagerholm, Susanna Carola (Frontiers in Immunology, 2019)
β2-integrins are essential for immune system function because they mediate immune cell adhesion and signaling. Consequently, a loss of β2-integrin expression or function causes the immunodeficiency disorders, Leukocyte Adhesion Deficiency (LAD) type I and III. LAD-III is caused by mutations in an important integrin regulator, kindlin-3, but exactly how kindlin-3 regulates leukocyte adhesion has remained incompletely understood. Here we demonstrate that mutation of the kindlin-3 binding site in the β2-integrin (TTT/AAA-β2-integrin knock-in mouse / KI) abolishes activation of the actin-regulated myocardin related transcription factor A / serum response factor (MRTF-A/SRF) signaling pathway in dendritic cells and MRTF-A/SRF-dependent gene expression. We show that Ras homolog gene family, member A (RhoA) activation and filamentous-actin (F-actin) polymerization is abolished in murine TTT/AAA-β2-integrin KI dendritic cells, which leads to a failure of MRTF-A to localize to the cell nucleus to coactivate genes together with SRF. In addition, we show that dendritic cell gene expression, adhesion and integrin-mediated traction forces on ligand coated surfaces is dependent on the MRTF-A/SRF signaling pathway. The participation of 2-integrin and kindlin-3-mediated cell adhesion in the regulation of the ubiquitous MRTF-A/SRF signaling pathway in immune cells may help explain the role of 2-integrin and kindlin-3 in integrin-mediated gene regulation and immune system function.